Avaliação da expressão do receptor do tipo 2 de Neuromedina U no hipotálamo em modelo murino de ciclagem de peso e compulsão alimentar - Alessandra Rocha Job (2022)
Weight cycling is a term used for the profile of weight loss and gain resulting from restrictive diets that can harm health in addition to the development of eating disorders. One of these disorders is binge eating (BED) which affects about 3.5% of women and 2% of men. The development of TCA is multifactorial and its neurobiology is not yet fully elucidated, however recent evidence points to the participation of the neuropeptide Neuromedin U and its receptors. Neuromedin U receptor type 2 (NMUR2) deficiency in the mouse hypothalamus leads to a higher intake of hyper palatable foods. The aim of this study was to verify whether mice submitted to different diets that can stimulate weight cycling and/or binge eating cause changes in anxiety and compulsion-like behaviors, correlating with NMUR2 protein abundance in the hypothalamus. Adult male C57BL/6J mice were divided into four groups and submitted to 4 different types of diet for a period of 6 weeks. Caloric restriction consisted of offering 60% of the usual amount of commercial food and the Oreo cookie was used as a hyper palatable food. The diet binge 1 (CP1) group received the Oreo along with the standard chow, alternating with weeks of calorie restriction. The diet binge 2 (CP2) group received standard chow alternating with weeks of calorie restriction. The binge eating (CA) group received standard chow along with Oreo weekly. The control group (CTRL) received standard diet only. The study evaluated whether the diets altered food consumption, induced weight cycling and/or binge eating, in addition to the development of anxious/compulsive behavior by the elevated plus maze (LCE) and "marble burying" tests. The results indicate that CP1 and CP2 presented weight cycling during the cycles and that the calories ingested at the end of the treatment were statistically superior to the other groups. Feed efficiency was calculated and it was observed that weight cycling decreases this efficiency, the opposite being observed when there was no cycling. The groups showed changes in the time spent in the open arms in the LCE test, but the CP1 group remained statistically longer in the closed arms. The marble burying test showed that CP1 and CA buried statistically more marbles in the first 10 minutes of the test when compared to the other groups. The protein levels of NMUR2 in the hypothalamus did not show statistical differences between the groups. The study, therefore, suggests that weight cycling is associated with increased caloric intake, decreased feed efficiency, anxious-like behavior pattern, but without significant changes in NMUR2 protein abundance in the hypothalamus.